SOCS3 regulation by microRNAs, cytokines and HCV - Collins, Aideen (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2012)
The Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway is the principal signalling mechanism for a wide array of cytokines. Dysregulation of JAK-STAT pathway has been noted in cancer and chronic viral disease. Suppressors of cytokine signalling (SOCS) proteins negatively regulate the JAK-STAT pathway by inhibiting JAKs and STATs and/or targeting them for proteasomal degradation. Although SOCS are important regulators of the JAK-STAT pathway, their own regulation has not been fully investigated and is the focus of this thesis.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.